Pengembangan Bahan Ajar Teks Eksplanasi Bermuatan Ekologi untuk Mendukung Pencapaian Profil Pelajar Pancasila untuk SMK - Deden Indra; Dyah Werdiningsih (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research aims to develop ecology-themed explanatory text teaching materials to support the achievement of the Pancasila Student Profile for vocational high schools (SMK). The teaching materials are designed to raise environmental awareness and foster sensitivity towards ecological issues. The development process follows the 4D model (Define, Design, Develop, Disseminate), focusing on the first three phases. Data collection techniques include questionnaires for students through purposive sampling and interviews with Indonesian language teachers. The results show that the teaching materials have a significant potential to be used in vocational education, integrating essential ecological knowledge with practical skills. This research underlines the importance of incorporating sustainable education in vocational curricula, ensuring students are equipped to face both the workforce and further education with an awareness of environmental challenges.